STUDI KESELAMATAN DAN KESEHATAN KERJA DALAM MENGGUNAKAN TEKNOLOGI NYAPAR UNTUK PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN - Valmando, Victor R; Hardiansyah, Gusti; Manurung, Togar Fernando (Universitas Tanjungpura, 2019)
This study aims to obtain information about work complaints and the level of risk of posture when using Nyapar technology, and analyzed the effectiveness of fire extinguisher formation images based on the superiority of blackouts and officer work safety. The method used is the survey. A data throught the distribution of the questionnaire NBM and literature study. The results showed that there 9 complaints of body posture on the use of a manual extinguisher, and 10 postures on the use of deep peat extinguisher and 0 complaints in the mounting automatically extinguisher. All complaints are included in the low injury risk category. The effectiveness of the border formation by Hardiansyah et al. (2016) can prevent fire and maintain the safety of firefighters with a semicircular form of burned area. The formation the border by Sambusir (2016) only prevents fires in front of the border areal and is difficult to extinguish fires that move on the left and right side outside the protected areal. The Formations around the fire (Hardiansyah et al. 2016 and Sambusir, 2016) have the same shape so that outages are more effective because of the position of extinguishers that surround the fire and maintain the safety of officer. The combination formation by Hardiansyah et al. (2016) can extinguish the fire in a large area and the safety of officers is protected, just need 2 additional water pump machines so that performance of the 17 extinguishing units remains optimal. The combination formation by Sambusir (2016) can extinguish the fire over a large area, just need to change positions between manual officer firefighters with automated extinguishers to side by side without changing the shape of the formation so as to protect the work safety of officers.Keywords: NBM, Safety work, Technology Nyapar, The Formation of the Fire Brigade